2016
DOI: 10.1371/journal.pone.0168709
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Pro-Inflammatory Cytokines Are Not Associated with Senescence Marker p16INK4a or Predictive of Intracellular Emtricitabine/Tenofovir Metabolite and Endogenous Nucleotide Exposures in Adults with HIV Infection

Abstract: ObjectivesAs the HIV-infected population ages, the role of cellular senescence and inflammation on co-morbid conditions and pharmacotherapy is increasingly of interest. p16INK4a expression, a marker for aging and senescence in T-cells, is associated with lower intracellular concentrations of endogenous nucleotides (EN) and nucleos(t)ide reverse transcriptase inhibitors (NRTIs). This study expands on these findings by determining whether inflammation is contributing to the association of p16INK4a expression wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…We have shown that expression of p16 INK4a , a tumor suppressor gene associated with cellular senescence (25), is associated with increased tenofovir diphosphate (TFVdp) and emtricitabine triphosphate (FTCtp) intracellular clearance, i.e., lower intracellular concentrations, among HIV-positive men and women ranging in age from 20 to 73 years (26,27). We did not, however, find associations between p16 INK4a expression and a panel of proinflammatory cytokines in our virally suppressed population (28).…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…We have shown that expression of p16 INK4a , a tumor suppressor gene associated with cellular senescence (25), is associated with increased tenofovir diphosphate (TFVdp) and emtricitabine triphosphate (FTCtp) intracellular clearance, i.e., lower intracellular concentrations, among HIV-positive men and women ranging in age from 20 to 73 years (26,27). We did not, however, find associations between p16 INK4a expression and a panel of proinflammatory cytokines in our virally suppressed population (28).…”
contrasting
confidence: 61%
“…First, log-rank tests were performed to compare the distributions of the ratios. This approach was used as some of the ratios had observations below the limit of quantification (BLQ) (28). To right-censor these observations and allow use of a log-rank test, ratios were subtracted from a value arbitrarily larger than the maximum of the ratios, as suggested by Gillespie et al (29).…”
Section: Methodsmentioning
confidence: 99%
“…p16 INK4a + cells isolated from adipose tissue exhibit elevated expression of pro-inflammatory senescence-associated secretory phenotype (SASP) products compared to cells from the same tissues not expressing p16 INK4a (3,11,26,28). However, the relation between p16 INK4a and the SASP is nuanced and by p16 INK4a overexpression may not consistently activate a SASP (30,31). Whether driven through SASP-dependent mechanisms or not, collectively these data support a model in which p16 INK4a + cells shorten healthy lifespan and negatively impact function with age in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Such markers are important to evaluate individual variation in the rate of aging in human populations and the impact of interventions that target the aging process. Efforts to estimate the burden of senescence have focused on RNA levels of the cell cycle regulator, p16 INK4a , and mediators of the senescence-associated secretory phenotype (SASP) (Sanoff et al 2014;Maas et al 2016). These mediators include inflammatory cytokines such as IL-6 and IL-8.…”
Section: Introductionmentioning
confidence: 99%